A new enzymatic variant of Leishmania (vianna) guyanensis found in isolates from patients in Santar?m, Par? state, Brazil - Jennings, Yara L?cia Lins (Instituto de Medicina Tropical de S?o Paulo, 2016)
Trabalho apresentado no Annual Meeting on Basic Research in Chagas Disease, 30.; Meeting of the Brazilian Society of Protozoology, 19., 2003, Caxambu.